The impact of high altitude (hypobaric hypoxia) on insulin resistance in humans - Adeva-Andany, María M.; Adeva-Contreras, Lucia; Carneiro-Freire, Natalia; Ameneiros-Rodríguez, Eva; Vila-Altesor, Matilde; Calvo-Castro, Isabel (Journal of physiology and biochemistry, 2025)
Exposure to hypobaric hypoxia (high altitude) diminishes systemic tissue oxygenation. Tissue hypoxia induces insulin resistance and a metabolic switch that reduces oxidative phosphorylation and glucose storage while enhancing glycolysis. Similarly to hypobaric hypoxia, insulin resistance develops in normal humans undergoing normobaric hypoxia and in patients with obstructive sleep apnea. Following acute exposure to high altitude, insulin resistance returns to baseline values upon returning to sea level or when compensatory mechanisms restore tissue oxygenation. However, insulin resistance persists in subjects unable to achieve sufficient oxygen delivery to tissues. Likewise, long-term residents at high altitude develop persistent insulin resistance when compensatory mechanisms do not attain adequate tissue oxygenation. Among these subjects, insulin resistance may cause clinical complications, such as hypertriglyceridemia, reduced HDL-c, visceral obesity, metabolic dysfunction-associated steatotic liver disease, essential hypertension, type 2 diabetes, subclinical vascular injury, cardiovascular disease, and kidney disease. Impaired tissue oxygenation allows the stabilization of hypoxia-inducible factor-1 (HIF-1), a transcription factor that modulates the transcriptional activity of a number of genes to coordinate the physiological responses to tissue hypoxia. Among them, HIF-1 downregulates PPARG , that codes peroxisome proliferator-activated receptor-gamma (PPAR-γ) and PPARGCA , that codes PPAR-γ coactivator-1α, in order to enable insulin resistance and the metabolic switch from oxidative phosphorylation toward glycolysis. Key points • Exposure to high altitude (hypobaric hypoxia) reduces systemic tissue oxygenation. • Tissue hypoxia induces insulin resistance and a metabolic switch toward glycolysis. • A comparable metabolic adaptation occurs in patients with obstructive sleep apnea syndrome. • Hypoxia-related insulin resistance persists as long as tissue oxygenation is impaired.